2014
DOI: 10.1002/etep.2037
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effects of renewable and non-renewable DGs on DNEP from the reliability, uncertainty, and operational points of view by employing hybrid GA and OPF

Abstract: SUMMARYThis paper proposes an approach to evaluate the effects of renewable and non-renewable distributed generations (DGs) on distribution network expansion planning from the reliability, uncertainty, and operational viewpoints. This methodology aims to determine the optimal capacity reinforcement of distribution network to meet the load growth in the planning horizon subject to the technical and operational constraints in the presence of utility-owned DG units. The capacity reinforcement includes determining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 56 publications
(96 reference statements)
0
7
0
Order By: Relevance
“…As mentioned, there is no clear procedure for defining the scenarios, and the planner experience plays a major role in this procedure. In other studies,() to consider the uncertainties based on scenario analysis, 4 and 3 scenarios were defined, respectively. In the present case study, 6 possible scenarios are identified before the main simulation as follows.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…As mentioned, there is no clear procedure for defining the scenarios, and the planner experience plays a major role in this procedure. In other studies,() to consider the uncertainties based on scenario analysis, 4 and 3 scenarios were defined, respectively. In the present case study, 6 possible scenarios are identified before the main simulation as follows.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Equations 20 and 24 reveal the feedback relation between the block JK and the block consisting of the rest of the power system dynamic components, which can be drawn accordingly in Figure 1. Equation 20 shows the transfer function in the forward path of the close-loop system while Equation 24 demonstrates the transfer function in the feedback path of the close-loop system. Each block has its own voltage components as outputs, and its inputs are composed of its own control variables and the voltage outputs from the other block.…”
Section: Building Feedback Modelmentioning
confidence: 99%
“…In modern power system grid, renewable energy sources (RES) are giving attractive solutions for the future and further technology advancement is in process to enhance energy generation. [1][2][3][4][5][6] The RES have possibility to play an important role in the modern smart grid technology. The contribution and share of their RES in energy production has significantly increased in the last decade.…”
Section: Introductionmentioning
confidence: 99%